2018
DOI: 10.3892/ol.2018.8323
|View full text |Cite
|
Sign up to set email alerts
|

Target‑specific delivery of oxaliplatin to HER2‑positive gastric cancer cells in�vivo using oxaliplatin‑au‑fe3o4‑herceptin nanoparticles

Abstract: Abstract. Gastric cancer is the fourth most common malignancy globally. In order to decrease the dosage and side effects of conventional chemotherapy, and achieve improved benefits from molecular targeted therapy, novel drug delivery systems were developed in the present study. Oxaliplatin-Au-Fe 3 O 4 -Herceptin ® acts as a dual-functional nanoparticles (NPs) conjugate and possesses the capability of human epithelial growth factor receptor 2 (HER2) targeting and oxaliplatin delivery. The 8-20 nm Au-Fe 3 O 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The first attempt in vivo utilizing MNPs as a carrier for Oxaliplatin was performed to improve the colon cancer treatment responses by Liu et al [ 108 ]. It was demonstrated that Au-Fe 3 O 4 -Herceptin MNPs as a carrier for Oxaliplatin acted as dual-functional NPs conjugated and could oxaliplatin delivery and human epithelial growth factor receptor 2 targetings (HER2).…”
Section: Main Textmentioning
confidence: 99%
“…The first attempt in vivo utilizing MNPs as a carrier for Oxaliplatin was performed to improve the colon cancer treatment responses by Liu et al [ 108 ]. It was demonstrated that Au-Fe 3 O 4 -Herceptin MNPs as a carrier for Oxaliplatin acted as dual-functional NPs conjugated and could oxaliplatin delivery and human epithelial growth factor receptor 2 targetings (HER2).…”
Section: Main Textmentioning
confidence: 99%
“…The nanocomposite has probes for mass spectroscopy and nuclear magnetic resonance imaging as well as a drug-release assay that releases oxaliplatin (a breast cancer drug) in an acidic medium. The pH-controlled drug release lowers the dosage and period of administration for patients, thus reducing side effects and build-up of drug resistance in patients [ 135 ].…”
Section: Iron–gold Bifunctional Nanoparticlesmentioning
confidence: 99%
“…Other HER2 targeting strategies were also proposed in the nanotechnology realm. [28][29][30][31][32] Christopher et al reported dual HER2 targeting nanoparticles with trastuzumab and liposomal-encapsulated doxorubicin (MM-302) demonstrated synergistic targeting and anti-tumor activity in breast cancer and gastric cancer. 33 By targeting different domains of the HER2 receptor, MM-302 and trastuzumab could simultaneously bind to HER2-overexpressing tumor cells.…”
Section: Enhanced Gastric Cancer Targeted Imaging/drug Deliverymentioning
confidence: 99%